Family and working life in the 21st century - Family and working life 2003 - Bernhardt, Eva (Stockholm University, 2007)
The project 'Family and Working Life in Sweden' (YAPS) started in 1998. The aim of the project was to build up a longitudinal data base for studies of the mutual connection of values and demographic behaviour.
The first wave was carried out in the spring of 1999. Based on a nationally representative sample, 3 408 individuals aged 22, 26 and 30 were asked to respond to a mail questionnaire that included questions about their plans, expectations and attitudes regarding family and working life. Factual information about their current situation and background characteristics was also included. In addition to the main sample of young adults born in Sweden with two Swedish-born parents, there was a smaller sample of young adults born in Sweden with one or both parents born in Poland or in Turkey.
Out of the 2 273 respondents in the 1999 survey, 78 per cent also participated in the second wave of the survey, which took place in May-June 2003. The second wave also include a new sample of 22 year old individuals with two Swedish-born parents.
A third wave of the survey was carried out during the spring 2009.
Except information collected through the questionnaires a number of background variables are collected from Statistic Sweden's register over the total population (RTB) and register of education.

The respons rate for the 1999 survey was 67% for the sample with Swedish-born parents, 60% for respondents with Polish background and 49% for respondents withTurkish background. For the 2003 survey the response rate for respondents with Swedish-born parents was 72% - 78% for respondents who also participated in the 1999 survey and 60% for the new sample (born in 1980) - and 67% for the second-generation sample (69% for respondents with Polish background and 65% for respondents with Turkish background).

Projektet 'Familj och arbetsliv på 2000-talet' (YAPS) påbörjades 1998. Syftet var att bygga upp en longitudinell databas för studier av det ömsesidiga sambandet mellan värderingar och demografiskt beteende. De värderingar man har påverkar hur man fattar avgörande beslut om t ex att flytta ihop med en partner, skaffa barn eller byta jobb. I projektet analyseras dels värderingars betydelse för parbildning och barnafödande i den tidiga vuxenfasen (upp till 35 års ålder); dels hur värderingar avseende familj och arbete förändras över tiden beroende på en förändrad familjesituation. För att göra detta krävs paneldata, dvs att man har uppgifter för samma individer vid två eller flera tidpunkter. Därigenom kan man skilja mellan selektions- och adaptionseffekter.
Den första enkätundersökningen genomfördes våren 1999 och riktades till individer som var 22, 26 eller 30 år vid undersökningstillfället. Det fanns två olika urval, ett bestående av individer med två Sverige-födda föräldrar, och ett med individer med en eller båda föräldrarna födda i Polen eller Turkiet. En andra frågeomgång genomfördes våren 2003, då respondenterna var fyra år äldre. I 2003 års undersökning ingår för Sverige-urvalet även en ny grupp 22-åringar. En tredje datainsamling ägde rum under våren 2009.
Förutom variabler som samlats in via enkäterna har ett antal bakgrundsvariabler hämtats från SCBs register över totalbefolkningen (RTB) och SCBs utbildningsregister. Dessa uppgifter avser januari 1999 resp. januari 2003.

Svarsfrekvensen för 1999 års undersökning var 67% för Sverige-urvalet, 60% för respondenter med polsk bakgrund och 49% för respondenter med turkisk bakgrund. I 2003 års undersökning var svarsfrekvensen för Sverige-urvalet 72% - 78% för respondenter som också deltagit i 1999 års undersökning och 60% för det nya urvalet (födda 1980) - och för andragenerationsurvalet 67% (69% för de med polsk bakgrund och 65% för de med turkisk bakgrund).
Familj och arbetsliv på 2000-talet - Familj och arbetsliv 2003
YAPS - Young Adult Panel Study
Keywords: women's role; kvinnoroll; residential mobility; flyttningsbenägenhet; children; barn; cultural identity; kulturell identitet; job satisfaction; arbetstillfredsställelse; marriage; äktenskap; parental role; föräldraroll; domestic responsibilities; hushållsansvar; child care; barnomsorg; national identity; nationell identitet; immigrants; invandrare; citizenship; medborgarskap; living conditions; levnadsförhållanden; family life; familjeliv; labour and employment; arbete och sysselsättning; educational background; utbildningsbakgrund; marital status; civilstånd; childbirth; barnafödsel; spouses; makar; religious practice; religionsutövning; Adult; Vuxna; parental leave; föräldraledighet; families; familjer; working conditions; arbetsförhållanden; households; hushåll; working mothers; förvärvsarbetande mödrar; gender role; könsroll; Working conditions; Arbetsförhållanden; Gender and gender roles; Kön och könsroller; Family life and marriage; Familjeliv och äktenskap; Minorities; Minoriteter; Social Sciences; Samhällsvetenskap; Sociology; Sociologi